Synthesis, characterization, crystal structure, electrochemical studies and biological evaluation of metal complexes with thiosemicarbazone of glyoxylic acid - Huseynova, Mansura; Taslimi, Parham; Medjidov, Ajdar; Farzaliyev, Vagif; Aliyeva, Mahizar; Gondolova, Gulnar; Şahin, Onur; Yalçın, Bahattin; Sujayev, Afsun; Orman, Efe Baturhan; Özkaya, Ali Rıza; Gülçin, İlhami; et al. (Elsevier, 2018)
Cobalt and nickel nitrates form with thiosemicarbazone of glyoxylic acid (H(2)GAT) complexes of empirical composition Co(C3H4N3O2S)(2)center dot 2H(2)O, Ni(C3H4N3O2S)(2)center dot 2H(2)O and Ni(C3H6N3O2S)(2). X-ray diffraction studies have shown that the Co(HGAT)(2)center dot 2H(2)O, Ni(HGAT)(2)center dot 2H(2)O complexes are mononuclear, in which the coordination around the metal is octahedral, made up of two sulfur atoms, two nitrogen atoms and two oxygen atoms from two ligands. By the interaction of NiCl2 center dot H2O with 2-[2-(aminothioxomethyl)hydrazinyl] acetic acid (H(2)TAA) instead of the expected the metal thiosemicarbazonate complex with the hydrogenated on the azomethine group ligand was obtained. The redox properties of these compounds were also investigated by voltammetry on Pt in dimethylsulfoxide/tetrabutylammonium perchlorate. These thiosemicarbazone of glyoxylic acid derivatives had effective inhibition against alpha-glycosidase, cytosolic carbonic anhydrase I and II isoenzymes, butyrylcholinesterase and acetylcholinesterase. K-i values were found as 26.12-36.58 nM for hCA I, 20.73-40.78 nM for hCA II, 184.30-642.18 nM for AChE, 123.67-342.37 nM for BChE, and 14.66-45.62 nM for alpha-glycosidase. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Thiosemicarbazone; Carbonic anhydrase; Cholinesterase; Glycosidase; Enzyme inhibition